An exploration of teachers’ and leaders’ perceptions of their collaborative working and learning : the case of three general upper secondary schools in Finland - Machala, Molly (2021)
Educational leadership is an abstract concept that is still often discussed from the perspective that it can be understood, as through roles, practices, or outcomes (Dinh et al., 2014). However, the present study and its results provide a better understanding of educational collaborative leadership as both a process and an outcome. Viewing this phenomenon as the synergy of collaborative working and learning where both individual and collective endeavors are essential, as well as leadership that is co-created through meaningful interactions between stakeholders, can provide opportunities for educational organizations to respond to increasing global complexity and solve wicked problems (Jäppinen & Ciussi, 2016; Uhl-Bien, 2006; Packer & Goicoechea, 2000). This study was carried out as a part of a 2018-2021 project for the development of teacher education, led by the University of Jyväskylä and funded by the Ministry of Education and Culture, entitled KAJO. In conjunction with this project’s aim of strengthening the leadership skills of educators and educators in training, the present study aims to gain insight into collaborative leadership competence by exploring the relationship between teachers’ and leaders’ perceptions of their own collaborative working and learning when solving a wicked problem. Quantitative survey data was gathered from Finnish teachers (N=54) and leaders (N=8) across three general upper secondary schools, under one education provider, in an urban area of Finland. Participants were asked to rate their level of agreement towards statements that described their perceptions of their collaborative working and learning processes and outcomes. The findings of this study revealed that both teachers and leaders expressed agreement towards each statement, suggesting a collaborative leadership competence within the collective. More specifically, within the collaborative working dimension, it was found that leaders expressed more positive perceptions than teachers and no relationship between the demographic variables of age, gender, or work experience and the collaborative working dimension was found. Within the collaborative learning dimension, there was no significant difference between teachers’ and leaders’ perceptions, however, it was found that male leaders express more positive perceptions than female leaders. Additionally, the results showed that teachers and leaders both rated the same statement with the highest overall agreement and the same statement with the lowest overall agreement in both dimensions of collaborative working and learning.